Investigation of Slit Link Behavior with Wide-Flange (WF) Sections in Eccentrically Braced Frames (EBFs) - Wilson Meynerd Rafael, Jusuf; Suswanto, Budi; Chiu, Chien-Kuo; Iranata, Data; R. Amalia, Aniendhita; Ghifari, Fikri (Salehan Institute of Higher Education, 2026)
This study investigates the seismic performance of slit link configurations using wide-flange (WF) sections within eccentrically braced frames (EBFs), addressing the limited application of slit geometries in practical steel construction. The objective is to evaluate the influence of slit shape and width on shear strength, ductility, and energy dissipation, while ensuring damage localization within the link element. Six analytical models were developed, including conventional links (CV and CV-ST) and slit variants (SL-1 to SL-4), and analyzed through nonlinear finite element simulations in ABAQUS under the AISC 341-22 cyclic loading protocol. The analysis focused on stress distribution, hysteretic response, backbone curve stability, and energy dissipation. Results show that conventional links provide higher peak shear strength and energy absorption but transmit stresses into adjacent members, increasing repair complexity. In contrast, slit links confine plastic deformation within the link region, enhancing ductility and repairability at the expense of reduced strength. Among the slit variants, the parabolic slit (SL-4) demonstrated smoother stress redistribution and improved cyclic stability compared to rectangular slits. The novelty of this research lies in embedding slit geometries directly into WF profiles, offering a cost-effective fuse mechanism that bridges theoretical slit damper concepts with real-world EBF applications.